Effect of Green Tea Intake on some Inflammatory and Physiological Markers in Men (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Background:  The daily consumption of green tea is one of the most important beverages that contains many bioactive compounds, such as polyphenols and flavonoids, in large proportions. It has important health and disease prevention benefits and has antioxidant and anti-inflammatory properties and plays an important role in preventing and preserving the structure and function of body cells.  Our study was designed to investigate the effect of daily green tea intake on inflammatory markers, including IL-2, IL-6, and IL-12, as well as TNF-α, C-reactive protein, lipid profile, glucose status, and markers of liver, kidney, and heart function in men in Erbil.Materials and Methods: The study involved 21 healthy male volunteers, aged between 21 and 40 years, who consumed two cups of green tea daily and assessed inflammatory markers and physiological and biochemical tests by comparing the results before and after four weeks of daily intake of green tea. Results:Serological results of blood samples after 4 weeks of daily intake of green tea revealed a significant reduction (P < 0.001, P < 0.005) in IL-2, IL-6, IL-12, TNF-α, and C-reactive protein, and showed a significant reduction in blood glucose, HbA1c, TG, TC, and LDL cholesterol. It also showed significant reductions in liver, kidney and cardiac function.Conclusion: Our findings suggest that daily intake of green tea reduces the levels of inflammatory markers, reduces the blood lipid and sugar profiles, improves the physiological functions of the liver, kidneys and heart, and increases the effectiveness and activity of the body's immune system.